The hunchback of Notre Dame [videorecording (DVD)] - Trousdale, Gary; Wise, Kirk; Hulce, Tom, 1953-; Jay, Tony. 1933-2006; Moore, Demi; Hugo, Victor, 1802-1885 (Disney DVD : Distributed by Buena Vista Home Entertainment, 2002)
Quasimodo ventures from his tower to the joyous festival of fools, but the crowd turns cruel and rejects him because of the way he looks. The gypsy Esmeralda rescues him and he finds himself battling to save the people and the city he loves--while reminding us to see people as they are rather than how they appear.